Experiences of School as a Mediator between Interpersonal Competence and Happiness in Adolescents - Baytemir, Kemal (Anales de Psicología / Annals of Psychology, 2019)
The main purpose of this research is to examine the mediating role of the perception of school experiences in the relationship between interpersonal competence and happiness in adolescent. The participants in the study consisted of a total of 268 students, 104 females (39%) and 164 males (61%), attending various high schools in a city in the mid-Black Sea region. The participating students’ ages ranged between 14 and 18, with an average age of 16.22 (SD = 1.2). In order to gather data the “Interpersonal Competence Scale”, “Perceived School Experience Scale ” and “Oxford Happiness Scale” were used as measures. According to the results of the research, interpersonal competence predicts perceptions of school experience and happiness, perception of school experience predicts happiness. Analysis by structural equation modeling revealed that the perception of school experience has a partial mediating role in relationship between interpersonal competence and happiness in adolescents. The research findings are discussed within the context of the related literature and some suggestions are provided for researchers and practitioners in the field of mental health.